SAT0388 Effect of Etanercept Therapy on Lipid Profile in Patients with Psoriatic Arthritis. (10th June 2014) - Van Dongen, C.; Agca, R.; Trivino, L.; Vogelzang, E.; Nurmohamed, M.
Abstract : Background: Patients with rheumatoid arthritis have about a twofold risk to develop cardiovascular disease compared to the general population. There is accumulating evidence that anti-TNF therapy lowers this risk for cardiovascular disease in these patients by reducing inflammatory activity in the vascular wall. In addition, studies suggest that anti-TNF therapy might also decrease the cardiovascular risk through beneficial effects on the lipid metabolism. Psoriatic arthritis is also an auto-inflammatory disease, where the literature suggests that TNF inhibitors may lower the risk for cardiovascular disease by modulation of the lipid metabolism. However, thus far, this has not been investigated appropriately in this group of patients. Objectives: To explore the effect of TNF inhibiting therapy on lipid metabolism in patients with psoriatic arthritis. Methods: Observational cohort study to assess the long term safety and efficacy of therapy with etanercept in patients with psoriatic arthritis who did not respond to non-biological DMARD therapy. Results: The lipid metabolism was studied in a total of 157 consecutive patients (mean age (SD) was 47.1 (12.7) years and 75 (48%) males). The mean disease duration (range) at baseline was 9.0 (0.2 – 38.1) years. DAS, HAQ, CRP and ESR decreased significantly during therapy with anti-TNF. Outcomes that are related to lipid profile, such as HDL-cholesterol, LDL-cholesterol, triglycerides, total cholesterol/HDL-cholesterol ratio, Apo A-I and Apo B did not change significantly during follow up (Table 1 ). Conclusions: Therapy with etanercept in patients with psoriatic arthritis is effective and results in sustained improvement in DAS28, HAQ, CRP and ESR during five year therapy.However, serum lipid concentrations did not change significantly during therapy with etanercept. Therefore, lipids modulation can not explain the (postulated) favourable cardiovascular effects of TNF-blockers. Hence, further (mechanistic) research is necessary to explore the cardiovascular effects of TNF inhibitors in patients with psoriatic arthritis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5166